Access to credit and financial health: Evaluating the impact of debt collection - Julia Fonseca; Katherine Strair; Basit Zafar (Federal Reserve Bank of New York, 2017)
Despite the prevalence of debt collection and the intense regulatory activity surrounding this industry, little is known about how these practices impact consumers. This paper conducts an empirical analysis of the effect of debt collection on consumer credit and on indicators of financial health, employing individual credit record data and a difference-in-differences research design that compares outcomes for consumers in states that increased the restrictiveness of legislation with those for consumers in the remaining states. We find consistent evidence that restricting collection activities leads to a decrease in access to credit and a deterioration in indicators of financial health. Moreover, our estimated treatment varies considerably with the borrower's age and baseline credit score, with effects concentrated primarily among borrowers with the lowest credit scores.
Keywords: D12; D18; G18; K30; 330; debt collection; financial well-being